Automatic Switching System for Submersible Motor Pump: Case Study of a Cocoa Processing Company in Ghana - Osei-Kwame, Emmanuel; Sam-Okyere, Yaw; Dwomoh, Lambert (MSD Institute, 2025)
Cocoa processing companies are pivotal to Ghana's economy and the sustainability of its cocoa industry. Cocoa processing companies transform raw cocoa beans into a paste-like form known as cocoa liquor, which serves as the foundation for various cocoa-based products. These operations require using pumps to supply water for different stages of production. Most of these companies are particularly concerned about potential pump failures and the associated costs of replacements. To mitigate this risk, they have developed a technique to protect the pumps from burnout. Currently, the existing pump protection system is manually operated and suffers from inaccuracies in switching times. Additionally, fluctuations in weather conditions pose further threats to the pumps' integrity. This research focuses on automating the pump protection system to address these issues effectively. In this project, a Programmable Logic Controller (PLC) was utilized to design an automated protection system. The control program was simulated using RSLogix Micro Starter Lite to verify its functionality. Simulation results demonstrated that the system provides effective automatic protection for the pumps, thereby enhancing their operational efficiency and equipment longevity.